Impact of catheter ablation on HFpEF in people with comorbid atrial fibrillation and HFpEF using invasive haemodynamic testing. (25th November 2020) - Sugumar, H; Nanayakkara, S; Vizi, D; Chieng, D; Leet, A; Mariani, J; Taylor, A; Kalman, J; Kistler, P; Ling, L
Abstract: Background: The impact of catheter ablation (CA) for atrial fibrillation (AF) in patients with heart failure with preserved ejection fraction (HFpEF) is unknown. Objectives: To determine whether CA for AF reverses adverse haemodynamic changes associated with HFpEF. Methods: Consecutive consenting patients with EF ≥50% scheduled for index CA underwent baseline exercise right heart catheterisation (exRHC), cardiac output (CO) measurement, cardiac MRI, echocardiogram, QOL questionnaires and BNP testing. HFpEF was defined by resting pulmonary capillary wedge pressure (PCWP) ≥15mmHg or peak exercise PCWP ≥25 mmHg during exRHC. Patients with HFpEF were offered follow-up exRHC ≥6 months post-CA. Results: Of 252 patients scheduled for CA between April 2017 and Sept 2019, 131 (51.9%) qualified for inclusion, 65 (49.6%) consented to exRHC and 11 (16.9%) were excluded due to a subsequent decrease in EF (10) and uncontrolled hypertension (1). Fifty-four underwent exRHC, with 35 (65%) meeting criteria for HFpEF. Of them 26 (74.3%) who underwent CA, 20 (77%) had a follow up exRHC at 12±6 months follow-up, showing an overall decrease in peak exercise PCWP from 30.3±4.2 to 26.8±4.7 mmHg (p<0.05). Patients without arrhythmia recurrence showed significant improvements in peak exercise PCWP (29.2±3.7 to 22.9±2.0 mmHg (p<0.01). Their cardiac output increased from 10.3±3.0 to 12.1±4.0 mmHg p=0.1), and BNP decreased from (94.6±101.6 to 38.0±34.0 mmHg (p=0.06), whereas those with arrhythmia recurrence did not. Overall, 9 patients (45.0%) no longer met criteria for HFpEF. Conclusion: There is a high prevalence of HFpEF in people referred for AF ablation. Successful CA for AF reverses the adverse haemodynamic changes associated with HFpEF Funding Acknowledgement: Type of funding source: Public grant(s) – National budget only. Main funding source(s): NHMRC, NHF, RACP